Tổng hợp thăm dò hoạt tính sinh học phức chất của europi (III) với L-tryptophan - Uyển và cộng sự, Nguyễn Trọng (Vietnam Journal of Chemistry, 2014)
The complex of of Europium with L-Tryptophan has been isolated in solid state. The structure of the complex was determined by thermal decomposition and IR spectral methods Biological activities of complex of Europium were studied